eHealth initiatives; the relationship between project work and institutional practice - Line Lundvoll Warth; Kari Dyb (BMC, 2019)
Abstract Background Large-scale, national eHealth services, such as the summary care record (SCR) and electronic prescriptions (e-prescriptions), have been implemented by project managers as Norwegian health authority initiatives. Few studies have been conducted on the large-scale implementation of eHealth services and the relationship between the implementers' work and the use of the tools in healthcare practices. Hence, there was a need to determine the project work with a focus on changes in practice. This study explores the implementation of the SCR and e-prescriptions from the perspective of project managers; how does the implementation work by project managers relate to institutional practices in large-scale initiatives? Methods Twenty-two semi-structured interviews were held with project managers in 2016 and 2018 and were recorded, transcribed, and coded according to the content. The analytical concepts of the "project" and "practice" were used to focus on tensions between the dimensions of time connecting historically established social practice and in situ actions. Results The eHealth initiatives were demonstrated to have been implemented as a part of the national strategy and achieved through close collaboration with the Norwegian Directorate of eHealth (NDE). Tensions arose in relation to task-oriented actions during the implementation of the project and the daily management thereafter. Further, the work tasks of the project managers were related to the dissemination of the tools while, in practice, the tools were related to actual use by professionals. The implementation of several projects simultaneously created tensions between the implementation of a tool and a specific practice, as well as between tools. Conclusion The objectives set out by the project managers in relation to their work should be viewed as temporary, whereas a long-term objective should apply to the use of the tools. Hence, the work of implementing eHealth initiatives might call for a renewed definition of the empirical object. Identifying factors that affect uptake, such as gaps between the intended use of an object and in situ actions or historically established activities, might expedite the future success of national eHealth initiatives. The social aspect of institutional practice has a direct bearing on the potential of a project to be implemented successfully.